Cancer Patients with Acute Coronary Syndrome Have Non-Superior Bleeding Risk Compared to Patients with Similar Characteristics - a Propensity Score Analysis from the ProACS Registry - Mano, T (2022)
Introduction: The management of acute coronary syndrome (ACS) in malignancy is challenging due to higher bleeding risk. Methods: We analyzed patients with cancer (active or in the previous five years) prospectively included in the ProACS registry between 2010 and 2019. Our aim was to assess safety (major bleeding, primary endpoint) and secondary efficacy endpoints (in-hospital mortality and combined in-hospital mortality, reinfarction and ischemic stroke) of ACS treatment. Propensity score matching analysis (1:1) was further performed to better understand predictors of outcomes. Results: We found 934 (5%) cancer patients out of a total of 18 845 patients with ACS. Cancer patients had more events: major bleeding (2.9% vs. 1.5%), in-hospital mortality (5.8% vs. 3.4%) and the combined endpoint (7.4% vs. 4.9%). The primary endpoint was related to cancer diagnosis (OR 1.97), previous bleeding (OR 7.09), hemoglobin level (OR 4.94), atrial fibrillation (OR 3.50), oral anticoagulation (OR 3.67) and renal dysfunction. Mortality and the combined secondary endpoint were associated with lower use of invasive coronary angiography and antiplatelet and neurohormonal blocker therapy. After propensity score matching (350 patients), there were no statistically significant differences in endpoints between the populations. Conclusion: Bleeding risk was not significant higher in the cancer population compared to patients with similar characteristics, nor were mortality or ischemic risk. The presence of cancer should not preclude simultaneous ACS treatment.